2016
DOI: 10.1016/j.mimet.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Identification of urinary tract pathogens after 3-hours urine culture by MALDI-TOF mass spectrometry

Abstract: Complicated urinary tract infections, such as pyelonephritis, may lead to sepsis. Rapid diagnosis is needed to identify the causative urinary pathogen and to verify the appropriate empirical antimicrobial therapy. We describe here a rapid identification method for urinary pathogens: urine is incubated on chocolate agar for 3h at 35°C with 5% CO2 and subjected to MALDI-TOF MS analysis by VITEK MS. Overall 207 screened clinical urine samples were tested in parallel with conventional urine culture. The method, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Direct analysis of clinical samples further increased the usefulness of this method by eliminating the time required for microorganism growth and isolation. Several studies have applied the technique to detect and identify microbial pathogens directly from urine (10)(11)(12)(13) and have revealed that clinicians would receive therapeutically helpful information for 96.1% of samples in less than 1 h (10,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Direct analysis of clinical samples further increased the usefulness of this method by eliminating the time required for microorganism growth and isolation. Several studies have applied the technique to detect and identify microbial pathogens directly from urine (10)(11)(12)(13) and have revealed that clinicians would receive therapeutically helpful information for 96.1% of samples in less than 1 h (10,14).…”
mentioning
confidence: 99%
“…Much effort has been spent to improve urine processing and to enhance the identification capability of MALDI-TOF MS by coupling it with rapid urine analysis (4,10,12,(14)(15)(16). This study aimed to establish and optimize a urine processing method to improve the analytical sensitivity and specificity of MALDI-TOF MS.…”
mentioning
confidence: 99%
“…This choice proved to be more relevant since the identification scores obtained were significantly improved with use of the Urinf database. Some of the recently published protocols require tedious prehandling, such as a preincubation step (15,16), dual filtration (16), or diafiltration (17), that would be difficult to implement in a clinical laboratory because of the substantial amount of incoming samples. It was estimated that only 40 to 60 min was necessary to carry out our entire procedure on up to 20 samples and to perform bacterial identification.…”
Section: Discussionmentioning
confidence: 99%
“…The confirmation of the identification of all isolates was performed by using MALDI-TOF MS as was previously described [19]. In brief, all isolates were activated in fresh Luria Bertani broth and grown overnight at 37° C. After that, isolates were grown on BHI agar 16 hours at 37º C and a sample of the growth was taken with a 1µL loop to the MALDI-TOF target plate.…”
Section: Maldi-tof-ms Based Identificationmentioning
confidence: 99%